Characterization of small single photon avalanche diode fabricated using standard 180 nm CMOS process for digital SiPM - Oh, Jinseok; Jeong, Hakcheon; Lee, Min Sun; Kwon, Inyong (Nuclear engineering and technology, 2024)
In this work, single photon avalanche diodes (SPADs) were fabricated using the standard 180 nm complementary metal-oxide semiconductor process. Their small size of 15–16 μ m and low operating voltage made it possible to easily integrate them with readout circuits for compact on-chip sensors, particularly those used in the radiation sensor network of a nuclear plant. Four architectures were proposed for the SPADs, with a shallow trench isolation (STI) guard ring and different depletion regions designed to demonstrate the main performance parameters in each experimental configuration. The wide absorption region structure with PSD and a deep N-well could achieve a uniform electric field, resulting in a stable dark count rate (DCR). Additionally, the STI guard ring was implanted to mitigate the premature edge breakdown. A breakdown voltage was achieved for a low operating voltage of 10.75 V. The DCR results showed 286.3 Hz per μm2 at an excess voltage of 0.04 V. A photon detection probability of 21.48% was obtained at 405 nm.